Non-capsulated Neisseria meningitidis sepsis in a paroxysmal nocturnal hemoglobinuria patient treated with ravulizumab: case report and review of the literature - Galli, Nicole; Pettine, Loredana; Panigada, Mauro; Daprai, Laura; Suriano, Grazia; Grancini, Anna; Barcellini, Wilma; Fattizzo, Bruno (Frontiers in Immunology, 2023)
Paroxysmal nocturnal haemoglobinuria (PNH) is a rare acquired haematopoietic stem cell disease characterized by complement-mediated intravascular hemolysis, thrombosis, and bone marrow failure. Eculizumab and ravulizumab are anti-C5 monoclonal antibodies that reduce hemolysis, anaemia and thrombotic risk, but are associated with increased risk of infection with encapsulated bacteria, including Neisseria meningitidis. We report a case of life-threatening infection by non-groupable Neisseria meningitidis in a young PNH patient treated with ravulizumab. Despite prompt admission to the intensive care unit, microbe isolation was delayed due to the negativity of capsular antigens, and the patient required intubation, dialysis, and transfusion support for pancytopenia. Notably, PNH disease activity remained controlled and no additional anti-C5 doses were administered. Increasing awareness regarding septic risk in PNH patients on complement inhibitors despite vaccinations is pivotal. A warning about serotypes generally not pathogenetic and not covered by vaccination, such as non-capsulated forms, is emerging.